Analysis of the causes and consequences that lead the NEW EPS to violate the right to health of its users, in the periods 2018 to 2020 (2021)
The right to health is a fundamental right, but it is violated in Colombia as a result of unjustified administrative procedures incurred by health promoting entities (EPS), these procedures are generally transferred to users, which puts in risk your physical and psychological condition and could even affect your life. It is important to mention that the State is the one who must guarantee the correct provision of the Health System in Colombia, exercising controls that allow access and efficient and timely care to the users of the health system. Taking into account that the Superintendency of Health is the body in charge of controlling, regulating, receiving and issuing measures related to the different situations presented by the users of the Health system, it has been evidenced in the last three years (2018 to 2020) that the NEW EPS is one of the entities with more complaints for the violation of the right to health, since the delay in its administrative procedures generated delays and damages for users, for which improvement measures and actions must be adopted that allow effective and efficient care.